Determining the Optimal Flowering Time in Rainfed Wheat Under Simultaneous Heat and Drought Stresses in Some Regions of Iran as Predicted by APSIM-Wheat Model - َArezu Shahbazi; Sara Abedini; Reza Deihimfard; Sajjad Rahimi-Moghaddam; Omid Noori (علوم محیطی)
Introduction: Drought and heat stress as the most important limiting factors in the production of crops and finally food security, have resulted from changing climate due to human interventions in increasing greenhouse gas emissions. It is also simulated that each 1 ◦C increase in temperature caused a 6% decline in global wheat production. The increase in temperature can further decline grain yield when occurred during the reproductive stage. The simultaneous effects of drought and heat during the growth stages, especially the flowering and grain filling stages, which are the most sensitive, can be more harmful than the individual effects and lead to a significant reduction in yield. The current study aimed at determining the optimal cultivar × sowing date in different climates to coincide the flowering date with optimum climaticconditions (temperature and rainfall) using a simulation modeling approach. Material and Methods: The current study was conducted in eight locations with different climates according to the GYGA (Global Yield Gap Atlas) methods. Dezful and Shushtar had warm and dry climates with high fluctuations in average seasonal temperature, Hamedan and Nahavand had mild and dry climates with medium fluctuations in average seasonal temperature, Khorramabad and Aligodarz had mild and dry climates with high fluctuations in average seasonal temperature and Zanjan and Khodabendeh had cold and dry climates with medium fluctuations in average seasonal temperature. Choosing the study locations was based on both areas under wheat cultivation and the diversity in their climates. In this research, several management methods including 4 sowing dates, 4 initial soil water​​, and 3 cultivars in 8 locations with different climates for 37 years (1980-2016) were investigated. A modified version of the APSIM-Wheat model was used in which a heat stress module could capture the impacts of heat stress on grain number and weight. The simulations were conducted under drought stress alone (rainfed) as well as the simultaneous drought and heat stress. Results and Discussion: The average grain yield under drought conditions was simulated at 2.99 tons per hectare, while the yield under simultaneous drought and heat stress was 2.44 tons per hectare, indicating a reduction of approximately 0.5 tons per hectare due to the combined effect of heat and drought stress. The mid-maturity cultivar had the highest yield reduction of 52% while the very early-maturity cultivar showed the lowest yield reduction of 0.16%. The wheat flowering time in cold regions occurred after the completion of flowering in warmer locations. In temperate climates, the occurrence of flowering dates was more extensive than in other locations. Overall, any delay in emergence under rainfed resulted in further yield reduction in all cultivars and locations. Conclusion: Under warm climates, an early-maturity cultivar along with early sowing could provide better environmental conditions for photosynthesis and plants could escape from terminal drought and heat stresses. In contrast, in cold climates, any delay in flowering date increases yield. In mild regions, using a mid-maturity cultivar resulted in late flowering dates and higher yields in spite of coinciding wheat with heat and drought for a short period of time.